Admission Control for Video Traffic Streams with Scaling CharacteristicsDOI: 10.14209/jcis.2002.1 - Pontes, Raniery; Coelho, Rosângela (Journal of Communication and Information Systems, 2015)
The impact of time-dependence or scaling characteristics on video acceptance regions is examined on this paper. We considered two different Call admission control (CAC) mechanisms: i) a descriptor-based CAC (DBCAC) mechanism and ii) a measurement-based CAC (MBCAC) mechanism. The proposed MBCAC is a hybrid measurement scheme that includes a Kalman filter and a real-time Hurst estimation based on wavelets. We investigated several buffer sizes and video sequences with different dependence degrees. Furthermore, for the accuracy of the Hurst (H) estimation, we developed a Hurst Estimator Package (HEP). This package consists of the estimators: Rescaled adjusted range (R/S), Higuchi and Abry-Veitch wavelet (AV). An important result showed that video traffic connection with long-range dependence (LRD) and short-range dependence (SRD) have similar admission regions.